2012
DOI: 10.3748/wjg.v18.i8.840
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fibroblast activation protein in human pancreatic adenocarcinoma and its clinicopathological significance

Abstract: FAP is highly expressed in carcinoma cells and fibroblasts in PDAC tissues, and its expression is associated with desmoplasia and worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 34 publications
8
115
1
6
Order By: Relevance
“…[31][32][33][34][35][36] In addition, the detection of pancreatic stellate cells immediately adjacent to pancreatic ductal adenocarcinoma epithelium correlates with adverse clinicopathological parameters. 6,7,37 Our group and others have shown that highly contractile pancreatic stellate cells can produce aligned collagen matrices in vitro, and the resultant topography can facilitate pancreatic ductal adenocarcinoma cancer cell migration. [38][39][40] Our immunohistochemical analysis suggests a positive correlation between alpha-smooth muscle actin expression and aligned collagen in the pancreatic ductal adenocarcinoma periductal stroma, which should be further validated on a larger patient cohort for potential mechanistic insight (Figure 4, Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35][36] In addition, the detection of pancreatic stellate cells immediately adjacent to pancreatic ductal adenocarcinoma epithelium correlates with adverse clinicopathological parameters. 6,7,37 Our group and others have shown that highly contractile pancreatic stellate cells can produce aligned collagen matrices in vitro, and the resultant topography can facilitate pancreatic ductal adenocarcinoma cancer cell migration. [38][39][40] Our immunohistochemical analysis suggests a positive correlation between alpha-smooth muscle actin expression and aligned collagen in the pancreatic ductal adenocarcinoma periductal stroma, which should be further validated on a larger patient cohort for potential mechanistic insight (Figure 4, Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…4 In a number of different cancer types, stromal properties have demonstrated importance in disease identification, progression, and patient prognosis. [5][6][7][8][9][10][11][12] Given the pronounced desmoplastic reaction in pancreatic ductal adenocarcinoma, a large number of recent research efforts have focused on elucidating stroma-cancer interactions for both nuanced insight into disease progression and for potential diagnostic, prognostic, or therapeutic targets. 13 The dominant extracellular matrix component of most tumor stromas, including that of pancreatic ductal adenocarcinoma, is fibrillar collagen.…”
mentioning
confidence: 99%
“…Moreover, this marker is upregulated when mesenchymal stem cells are recruited into growing tumors [21,22]. Tumor-associated stromal expression of FAP was found to be associated with more aggressive disease progression, and potential development of metastasis, recurrence, and death in colon and pancreatic cancers [23][24][25]. Previous studies in ovarian cancers treated with standard surgery followed by chemotherapy showed an association of FAP with advanced stage disease, lymph node metastasis, omental involvement, lymphovascular disease, and increased angiogenesis, but there is lack of data on the association of FAP with patient outcomes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Prominent presence of CAF FAP in the stroma of solid tumors is correlated to a poor prognosis in colon carcinoma and pancreatic adenocarcinoma [26,27] …”
Section: Fibroblast Activation Protein αmentioning
confidence: 99%